(untitled) (Ahkam: Jurnal Hukum Islam, 2022)
Marriage is seen as a sacred event and a significant milestone in human life, and religious components are crucial to its continuation. Marriage Law Number 1 of 1974 takes into account interfaith unions. But because their original dads frequently do not accept them, illegitimate children can cause issues in society with relation to accountability, such as who is responsible for providing for the children’s financial support, care, and education. In this research of legal ramifications and determining a child’s origin without using a DNA test are examined. The study adopts a normative legal approach. The study’s findings indicate that Article 43 Paragraph 1 of the Constitution regulates the requirements of life and defines what is meant by a child born outside of wedlock as having a legal status that is limited to a civil relationship with the mother and her family. Legally speaking, children’s financial and material well-being is the responsibility of their mother and her family. However, as noted in the Constitutional Court Decision No. 40/PPU-VIII/2010, biological fathers are also legally required to take care of, raise, and care for children born outside of marriage if they do not accept the child’s status